Parkinson Bureaucracy: An Analysis of Administrative Structure in Current Indonesia Cabinet System - Tiurma Shirley Panjaitan; Septia Dwi Cahyani; Sajida Sajida (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2025)
Leadership style has a significant impact on the development of Indonesia bureaucratic structure. In 2024, under the administration of Prabowo Subianto and Gibran Rakabuming, the number of ministers and deputy ministers increased significantly compared to previous administrations. This phenomenon is in line with Parkinson Bureaucracy theory, stating that a bureaucratic structure extends beyond practical necessity, resulting in inefficiency and possibly ineffectiveness, contrary to the principles of good governance. Bureaucratic growth often leads to unnecessary expenditures and budgetary waste due to overlapping responsibilities, preventing effective governance and service delivery. Therefore, this study aims to analyze the development of Parkinson Bureaucracy in the cabinet of Indonesia and analyze the effects on efficiency, reform in governance, and public service delivery. A systematic literature review method was used to analyze previous studies, policy analyses, and relevant data with a focus on determining the extent to which administrative structure are consistent with governance principles. The results showed that the enlarged cabinet structure contributed to increased inefficiencies and, concomitantly, greater coordination challenges and higher administrative overhead costs, limiting funds for public welfare investments. These structural inefficiencies underscore the urgent need for rightsizing and reforms aimed at optimizing roles, minimizing redundancies, and fostering accountability as well as transparency. Simplifying bureaucratic structure is important to improve responsiveness, decision-making processes, and efficiency outcomes in governance. Therefore, under the ideals of good governance, Indonesia must place priorities on reforms that increase the efficiency of public service orientation and structural complexity. This study emphasizes the urgent need for actions towards Parkinson bureaucracy.